Terrestrial habitat use by frogs and toads, Rana temporaria L. and Bufo bufo (L.), in West Norway - Karl Frafjord; Ingvar Byrkjedal (Fauna Norvegica)
Frogs and toads, Rana temporaria and Bufo bufo, are the most common amphibians in Norway, but little information is available on their distribution and numbers. We studied their habitat use during the terrestrial phase in West Norway (Rogaland to Møre and Romsdal counties) by examining all specimens in the collections of the Museum of Zoology, University of Bergen and by analyzing questionnaires. Frogs and toads were generally found at different sites, and both species were located together in only 10 sites (9.9 %). Differences in habitat use between the two species were mainly due to toads occupying coniferous forest or cultivated land below 200 m a.s.l. More frogs were found in deciduous forests and humid regions, at varying altitudes to above 1 000 m a.s.l.